Examining Conners Continuous Performance Test-3 (CPT-3) Embedded Performance Validity Indicators in an Adult Clinical Sample Referred for ADHD Evaluation. Issue 5 (4th July 2021) - Scimeca, Lauren M.; Holbrook, Lindsey; Rhoads, Tasha; Cerny, Brian M.; Jennette, Kyle J.; Resch, Zachary J.; Obolsky, Maximillian A.; Ovsiew, Gabriel P.; Soble, Jason R.
ABSTRACT: This study evaluated multiple previously-identified Continuous Performance Test-Third Edition (CPT-3) scores as embedded validity indicators (EVIs) among 201 adults undergoing neuropsychological evaluation for Attention-Deficit/Hyperactivity Disorder (ADHD) divided into valid (n = 169) and invalid (n = 32) groups based on seven criterion measures. Although 6/10 CPT-3 scores accurately detected invalidity, only two reached minimally acceptable classification accuracy of ≥0.70. The remaining four had unacceptably low accuracy (AUCs = 0.62–0.69) with 0.19–0.41 sensitivity at ≥0.90 specificity. Composite scores did not provide better classification accuracy than individual CPT-3 scores. In sum, CPT-3 individual and composite scores generally are not accurate PVTs among adults undergoing clinical evaluation for ADHD.